Sistem Informasi Akademik SDN 19 Pasar Ambacang Berbasis PHP dan Database - Syahputra, M.; Sunaryo, Nandra; Hanifa, Amalia (CV. Information Technology Training Center - Indonesia (ITTC), 2022)
The Academic Information System (SIA) is considered important in the world of education to help manage student information quickly and accurately. This study aims to design and develop an SIA that includes the collection and organization of student data, management of student attendance data, attendance history, and student attendance reports at SDN 19 Pasar Ambacang. The research method used is observation, interviews, and literature study. This application is built using PHP programming language with a MySQL database. The results of the study show that the developed SIA can help manage student and attendance data more efficiently and accurately. In addition, SIA can also provide information about student attendance history and attendance reports that can be used as a reference for teachers and administrative staff. This research can serve as a reference for other schools that want to implement SIA as a more effective and efficient solution for academic data management.